Cardiopulmonary interactions in left heart failure - Alvarado, Andrea C.; Pinsky, Michael R. (Frontiers in Physiology, 2023)
The primary impact of ventilation and ventilatory efforts on left ventricular (LV) function in left ventricular dysfunction relate to how changes in intrathoracic pressure (ITP) alter the pressure gradients for venous return into the chest and LV ejection out of the chest. Spontaneous inspiratory efforts by decreasing ITP increase both of these pressure gradients increasing venous blood flow and impeding LV ejection resulting in increased intrathoracic blood volume. In severe heart failure states when lung compliance is reduced, or airway resistance is increased these negative swings in ITP can be exacerbated leading to LV failure and acute cardiogenic pulmonary edema. By merely reversing these negative swings in ITP by the use of non-invasive continuous positive airway pressure (CPAP), these profoundly detrimental forces can be immediately reversed, and cardiovascular stability can be restored in moments. This forms the clinical rationale for the immediate use of CPAP for the treatment of acute cardiogenic pulmonary edema. Increasing ITP during positive pressure ventilation decreases the pressure gradients for venous return and LV ejection decreasing intrathoracic blood volume. In a hypovolemic patient even with LV dysfunction this can result in hypotension due to inadequate LV preload. Minor increases in ITP as occur using pressure-limited positive-pressure ventilation primarily reverse the increased LV afterload of negative swings in ITP and if fluid overload was already present, minimally alter cardiac output. The effect of changes in lung volume on LV function are related primarily to its effects on right ventricular (RV) function through changes in pulmonary vascular resistance and overdistention (hyperinflation). In acute lung injury with alveolar collapse, positive pressure ventilation may reduce pulmonary vascular resistance if alveolar recruitment predominates. Hyperinflation, however, impedes diastolic filling while simultaneously increasing pulmonary vascular resistance. Thus, increasing lung volume can reduce RV afterload by reversing hypoxic pulmonary vasoconstriction or increase afterload by overdistention. Hyperinflation can also impede RV filling. All of these processes can be readily identified at the bedside using echocardiography.